Avaliação de genes relacionados a motilidade celular em mulheres com endometriose profunda - Zanni, Pamela Cristina Mastellaro Delvas [UNIFESP] (2019)
Endometriosis is a common, benign, estrogen-dependent inflammatory disease and is a chronic gynecological disorder. The pathology affects approximately 10% of women in reproductive age and 35-50% of women who presents pelvic pain and infertility. The histological origin of endometriosis aims to explain the ability of endometrial tissue to develop ectopically. However, no consensus has been reached with regard to a single theory is able to explaining such capability. The retrograde menstruation is the oldest and accepted theory, but it does not explain how some women develop endometriosis and others do not, since all women have some degree of retrograde flow. Cell migration plays a central role in a wide variety of biological phenomena and contributes to the progression of most human diseases. In the adult organism the migration remains remarkable being essential for adequate immune response, wound repair and tissue homeostasis, nonetheless, in several pathologies it appears abnormally. However, little is known on the role of cellular motility mechanisms for the establishment and progression of endometriosis implants. The aim of this study was to evaluate, using RT-PCR, the expression of genes related to the cellular motility processes in primary cells derived from the endometrium of women with deep infiltrating endometriosis and women without the disease. For this, endometrial samples were obtained from volunteers of Pain Unit Pelvic and Endometriosis Department of Gynecology, Paulista Medical School of the Federal University of São Paulo (EPM-UNIFESP). Women between 29 and 35 years were recruited. For endometriosis group, women undergoing for surgery of IV stage endometriosis and the control group were composed of women submitted to laparoscopy for tubal ligation. The samples were cultured and stored for the RT-PCR realization in order to analyze the possible genes involved in the cellular motility process in primary cells derived from the endometrium of women with deep endometriosis. It was possible to observe that endometrial cells from women with deep endometriosis showed the gene CAV1 downregulated, a gene related to a tumor suppression; RHOB and PLD1 were upregulated, which are involved in cell migration and progression. In this sense, it is suggested that these genes may play an important role in the establishment and progression of endometriosis.